2019
DOI: 10.2147/idr.s206831
|View full text |Cite
|
Sign up to set email alerts
|

<p>Nine-year analysis of isolated pathogens and antibiotic susceptibilities of microbial keratitis from a large referral eye center in southern China</p>

Abstract: Purpose: To analyze the genus profile of isolated pathogens and antibiotic susceptibility trends of microbial keratitis over nine years at a large referral eye center in southern China. Methods: Data of corneal specimens from January 2010 to August 2018 of patients clinically diagnosed with infectious keratitis were obtained from the center’s microbiology database. Results with positive cultures along with antibiotic susceptibility were reviewed and analyzed. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 40 publications
(39 reference statements)
3
47
0
Order By: Relevance
“…Chinese research on corneal infections caused by SA confirmed the lowest resistance of the strains to neomycin (Wang et al 2016). The possibility of treatment with the aminoglycoside group was confirmed independently by studies by Blanco and coworkers and Lin and coworkers, which showed high susceptibility of those strains to chloramphenicol (Blanco et al 2013;Lin et al 2019). Our results also confirm the high susceptibility of the SA isolates to fluoroquinolones and chloramphenicol.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Chinese research on corneal infections caused by SA confirmed the lowest resistance of the strains to neomycin (Wang et al 2016). The possibility of treatment with the aminoglycoside group was confirmed independently by studies by Blanco and coworkers and Lin and coworkers, which showed high susceptibility of those strains to chloramphenicol (Blanco et al 2013;Lin et al 2019). Our results also confirm the high susceptibility of the SA isolates to fluoroquinolones and chloramphenicol.…”
Section: Discussionsupporting
confidence: 80%
“…Similar findings came from Canada and Europe (Asencio et al 2014;Assaad et al 2015). A Chinese analysis of corneal samples have provided that Gram-positive cocci (69.88%) are the most commonly isolated; nevertheless, a decreasing trend was observed over the nine years of the study (Lin et al 2019).…”
Section: Discussionsupporting
confidence: 75%
“… 21 Another large study conducted in the Southern China similarly reported a predominance of fungal keratitis in the region. 22 The variation of microorganisms is likely influenced by various factors, including the occupational risk of corneal trauma, agricultural industry, use of contact lens, national income and others. 1 8 …”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the broth was inoculated onto sheep blood agar and potato glucose agar for the growth of bacterial cultures and fungal cultures, respectively. [15][16][17]. All bacterial isolates were subjected to species identification on an automated microbiological system Vitek 2 Compact (BioMerieux, Inc., Marcy-l'Étoile, France); all fungi isolates were identified by experienced technicians according to fungal morphology.…”
Section: Methodsmentioning
confidence: 99%